A More Accurate Method to Estimate Aminoglycoside Clearance From Serum Creatinine in Patients With Spinal Cord Injury. (June 2015) - Lee, Jennifer P.; Truong, Thuy T.
Background: Current literature reports that the traditional methods overestimate renal function in spinal cord injury (SCI); however, there is no accepted standard method.Objective: This study evaluated 6 published methods against measured aminoglycoside (AG) drug clearance and determined the frequency with which each method would achieve target peak and trough AG concentrations within a specified range.Methods: A chart-based investigation was conducted at a hospital with a large SCI population, and a total of 35 patients met the inclusion criteria: a diagnosis of long-standing SCI, administration of AG via intravenous infusion, and at least one set of steady-state AG peak and trough concentrations. Pharmacokinetic analysis was performed to compare the measured AG clearance values against the values resulting from 6 methods of estimating the glomerular filtration rate (GFR). Patient-specific pharmacokinetic parameters were used to simulate steady-state peak and trough AG concentrations from doses derived from each method.Results: Compared with the other methods, the Lee–Dang method was found to be more accurate, with the smallest magnitude of variance from the measured AG clearance values. Five alternative methods significantly overestimated AG clearance, by approximately 70% to 160% ( P < .05). The Lee–Dang method underestimated AG clearance (by 10%), however not to a significant degree ( P = .079). Compared with the alternative methods, the Lee–Dang method resulted in a higher frequency of steady-state peak and trough AG concentrations within the target range specified.Conclusion: The Lee–Dang equation for predicting GFR was more accurate relative to the other methods in the study population of patients with long-term SCI.